Property Versus Misappropriation: Legal Protection for Databases in Korea - Sang Jo Jong; Junu Park (Washington University Journal of Law & Policy, 2002)
As a member of the international society which is now more interconnected than ever, Korea is experiencing a legal gap in the protection of databases. The commercial value of databases increased dramatically with the expanding use of computers and the Internet. As with other countries, Korea faces a choice in the legal forms of protection for databases: it can either extend the application of existing laws (i.e., patent and copyright protection) or create a new law (i.e., sui-generis database protection). In addition, Korea must choose either a property approach or a misappropriation approach for database protection. Although Korea attempted both approaches, there is still a controversy regarding which alternative will best guide Korea to prosperity in the digital age. This Essay argues that legislative proposals based on a property approach fail to cover the legal gap. A property approach has the potential to over-protect databases in Korea and negatively impact small innovators and the general public. Instead, this Essay submits that the misappropriation approach is the best alternative for the protection of databases in Korea. Unlike other countries such as the United States, Korea has not developed a misappropriation doctrine through case law or statutory provision. This lack of established law on the misappropriation doctrine points to a need for the enactment of a statutory provision explicitly prohibiting the misappropriation of databases in Korea.
Keywords: Information storage & amp; retrieval systems; Catalogs; Databases; Misappropriation of funds; South Korea